Pasture feeding strategy and milk fatty acid profile in small-scale dairy systems - PLATA-REYES, D A; JUÁREZ-DÁVILA, L E; MORALES-ALMARAZ, E; LÓPEZ-GONZÁLEZ, F.; FLORES-CALVETE, G.; ARRIAGA-JORDÃN, C M (The Indian Journal of Animal Sciences, 2021)
The effect of the pasture feeding strategy on the milk fatty acid profile of lactating cows in small-scale dairy farms was evaluated. Ten farms participated in the study, five farms grazed pastures a minimum of 8.0 h/d, and five were fed cut herbage. Supplementary feeds were similar. Results were analysed with Student “t” test. There were no statistical differences when fatty acids were grouped by chain length, or in the proportion of saturated fatty acids (SFA) or monounsaturated fatty acids (MUFA), but there were differences for polyunsaturated fatty acids (PUFA). Alpha-Linolenic acid (C18:3 n-3) was significantly higher in milk of grazing cows than in cows fed cut herbage. There were no differences in atherogenicity index nor in the Δ9 desaturase activity between pasture management strategies. In conclusion, grazing pastures results in milk with a more beneficial lipid profile for human health.